Whole-cell dependent biosynthesis of N- and S-oxides using human flavin containing monooxygenases expressing budding yeast. Issue 3 (June 2020) - Masuyama, Yuuka; Nishikawa, Miyu; Yasuda, Kaori; Sakaki, Toshiyuki; Ikushiro, Shinichi
Abstract: Flavin containing monooxygenases (FMOs) represent one of the predominant types of phase I drug metabolizing enzymes (DMEs), and thus play an important role in the metabolism of xeno- and endobiotics for the generation of their corresponding oxides. These oxides often display biological activities, however they are difficult to study since their chemical or biological synthesis is generally challenging even though only small amounts are required to evaluate their efficacy and safety. Previously, we constructed a DME expression system for cytochrome P450, UDP-glucuronosyltransferase (UGT), and sulfotransferase (SULT) using yeast cells, and successfully produced xenobiotic metabolites in a whole-cell dependent manner. In this study, we developed a heterologous expression system for human FMOs, including FMO1–FMO5, in Saccharomyces cerevisiae and examined its N- and S-oxide productivity. The recombinant yeast cells expressed each of the FMO successfully, and the FMO4 transformant produced N- and S-oxide metabolites at several milligrams per liter within 24 h. This whole-cell dependent biosynthesis enabled the production of N- and S-oxides without the use of the expensive cofactor NADPH. Such novel yeast expression system could be a powerful tool for the production of oxide metabolites. Graphical abstract: Image 1